Perancangan Aplikasi âLorong Gardenâ Sebagai Solusi Peningkatan Ekonomi Masyarakat Makassar dan Penghijaun Dunia - Sulfikar, Sufikar; Bazergan, Abdullah; Ali, M. Haider; Prastyo, Pulung Hendro (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2016)
"Lorong Garden" is a digital applications based Web client-server which is used by society in Makassar in promoting the information of Lorong Garden itself, such as the atmosphere the beauty of Lorong Garden, location, information for sale of the flowers, fruits and vegetables or plant herbal medicine equipped with available stock information so as to improve the local economy Makassar . "Lorong Garden" facilitates the tourists and the local society in finding the information of Lorong Garden specifically and increase the public interest in making the Lorong Garden that will help Go Green movement. This application consists of two part, they are website home page and administrator website of "Lorong Garden". The home page of "Lorong Garden" serves thr marketing information about the Lorong Garden. And the admnistrator website of "Lorong Garden" serves add information about the Lorong Garden to the page home page. The center of processing data is an internet service cloud computing therefore it can maximize the data mobilization easily. The results of application test shows that "Lorong garden" automatically adapt on any gadget, testing of the side of a Web server cloud computing running smoothly, as well as the system performance and functional of all menu and application run normally.